Usage of traditional medicines among elderly and prednisolone contamination - Ismail, Zabidah; Mohamed, Rafeezul; Mohd. Hassan, Mohd. Hashim; Wan Su, Kamaruzaman (Universiti Sains Malaysia, 2005)
The elderly consume many medications including traditional medicines. In 1986, it was found that 29% of elderly took traditional medicines although in 1996, the National Health Morbidity survey reported a 2.3% prevalence.However,studies from other countries showed much higher percentages. The Ministry of Health in Malaysia is concerned that some of these preparations maybe contaminated with steroids, antihistamines, hormones and other poisons. The aims of the study were to determine a). the health seeking behaviour of elderly Malays living in rural areas, b). the utilization of both modern and traditional medicines and c).the steroid content of the traditional medicines used. Methodology included interviews using structured questionnaires of elderly Malays living in rural areas of Kelantan, aged above 60 years. Samples of traditional medications ollected were sent to the Pharmacology Department, School of Medical Sciences, Universiti Sains Malaysia, for steroid content analysis using Thin Layer Chromatography. A total of 599 elderly respondents were interviewed comprising 62.4% females and 37.6% males. The 60-69 years cohort group made up 48.7%, followed by 70-79 years at 36.1% and the remainder 15.2% were more than 80 years. There were 82% of elderly taking medicines. The trends of utilization of modern and traditional medicine in the last two weeks among elderly were 59.3% and 40.9% respectively. The utilization of traditional medicine by rural elderly Malays was therefore much higher than that reported in the previous study and nearly similar to that of France and Australian studies. There were 102 samples of traditional medications collected and analysed for steroid content. Results showed that 27.5% were positive for prednisolone, 34.3% positive for unknown steroids (a total of 61.8%) and 38.2% were negative for both steroids. The present study therefore once again confirmed the high usage of traditional medicines where some of which are contaminated with steroids.